Exhaled nitric oxide monitoring does not reduce exacerbation frequency or inhaled corticosteroid dose in paediatric asthma: a randomised controlled trial. (10th August 2012) - Pike, Katharine; Selby, Anna; Price, Sophie; Warner, John; Connett, Gary; Legg, Julian; Lucas, Jane SA; Peters, Sheila; Buckley, Hannah; Magier, Krzysztof; Foote, Keith; Drew, Kirsty; et al.
Abstract Introduction Inhaled corticosteroid therapy (ICS) for asthma is currently modified according to symptoms and lung function. Fractional exhaled nitric oxide (FENO) has been demonstrated to be a non‐invasive marker of eosinophilic inflammation. Studies of FENO‐driven asthma management show variable success. Objectives This study aimed to evaluate whether monitoring FENO can improve outpatient management of children with moderate to severe asthma using a pragmatic design. Methods Children aged 6–17 years with moderate to severe asthma were recruited. Their asthma was stabilised before randomisation to FENO‐driven therapy or to a standard management group where therapy was driven by conventional markers of asthma control. ICS or long‐acting bronchodilator therapies were altered according to FENO levels in combination with reported symptoms in the FENO group. Participants were assessed 2 monthly for 12 months. ICS dose and exacerbation frequency change were compared between groups in an intention to treat analysis. Results Ninety children were randomised. No difference was found between the two groups in either change in corticosteroid dose or exacerbation frequency. Results were similar in a planned secondary analysis of atopic asthmatics. Conclusion FENO‐guided ICS titration does not appear to reduce corticosteroid usage or exacerbation frequency in paediatric outpatients with moderate to severe asthma. This may reflect limitations in FENO‐driven management algorithms, as there are now concerns that FENO levels relate to atopy as much as they relate to asthma control.